Towards large-scale in free-standing graphene and N-graphene sheets - Tatarova, E. (Sci Rep, 2017)
One of the greatest challenges in the commercialization of graphene and derivatives is production of high quality material in bulk quantities at low price and in a reproducible manner. The very limited control, or even lack of, over the synthesis process is one of the main problems of conventional approaches. Herein, we present a microwave plasma-enabled scalable route for continuous, large-scale fabrication of free-standing graphene and nitrogen doped graphene sheets. The method’s crucial advantage relies on harnessing unique plasma mechanisms to control the material and energy fluxes of the main building units at the atomic scale. By tailoring the high energy density plasma environment and complementarily applying in situ IR and soft UV radiation, a controllable selective synthesis of high quality graphene sheets at 2 mg/min yield with prescribed structural qualities was achieved. Raman spectroscopy, scanning electron microscopy, high resolution transmission electron microscopy, X-ray photoelectron spectroscopy and Near Edge X-ray-absorption fine-structure spectroscopy were used to probe the morphological, chemical and microstructural features of the produced material. The method described here is scalable and show a potential for controllable, large-scale fabrication of other graphene derivatives and promotes microwave plasmas as a competitive, green, and cost-effective alternative to presently used chemical methods.